Kerjasama Grebang Ratubangnegoro Kertowilangan dalam Perspektif SDGs : Peluang Intergrasi dalam Pengembangan Regional - Durrani Akmaputri Ardyani; Alya Syifa Maharani; Muhammad Misbahul Munir (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Abstract. Interregional cooperation is a strategic approach to addressing cross-boundary development challenges, particularly in supporting the achievement of the Sustainable Development Goals (SDGs). This study aims to examine the opportunities and challenges in implementing the Grebang Ratubangnegoro Kertowilangan cooperation, which involves 11 regencies/cities across East and Central Java. The research employs a Systematic Literature Review (SLR) method, by collecting and analyzing relevant academic articles from Google Scholar and other sources. This study is grounded in the Intergovernmental Relations theory by Agranoff and Radin (2014), which emphasizes the importance of collaboration and coordination across multiple levels of government in managing modern governance complexities, using five core principles as the analytical framework. The findings show that this cooperation has significant potential to accelerate infrastructure development, improve public service efficiency, and enhance regional economic competitiveness, especially in relation to SDG 11 and SDG 17. However, the initiative still faces major challenges, including weak institutional coordination, differing regional priorities, and limited resources. Therefore, strengthening institutional frameworks, establishing a joint secretariat, and integrating SDG indicators into interregional planning are recommended as strategic steps toward more effective and sustainable cooperation.